Los zorros vienen de noche - Nooteboom, Cees, 1933- (Nuevos tiempos (Madrid, Spain) ;, 2011)
Set in the cities and islands of the Mediterranean, and linked thematically, the eight stories The Foxes Come At Night read more like a novel, a meditation on memory, life and death.